TAMI-29. MULTIFACTORIAL UPREGULATION OF ID1 DRIVES DIPG INVASIVENESS AND IS THERAPEUTICALLY TARGETABLE - Nand Yadav, Viveka (Neuro Oncol, 2020)
Diffuse intrinsic pontine gliomas (DIPGs) are lethal brain tumors with no effective therapies other than radiation. Inhibitor of DNA binding (ID) proteins, key regulators of lineage commitment during embryogenesis, are implicated in tumorigenesis in multiple human cancers. Prior work showed that recurrent H3F3A and ACVR1 mutations increase ID1 expression in cultured astrocytes. However, this has not been validated in human DIPG. The regulation and targetability of ID1 in DIPG has not been explored either. Exome and transcriptome sequencing analysis of multi-focal DIPG tumors and normal brain tissue from autopsy (n=52) revealed that ID1 expression is significantly elevated in DIPG tissues. Higher ID1 expression correlates with reduced survival in DIPG patients and increased regional invasion in multi-focal autopsy samples. Analyses of developing mouse brain RNA/ChiP-Seq data revealed high ID1 expression and H3K27ac promoter binding in prenatal hind brain compared to all other prenatal and postnatal brain regions. ChIP-qPCR for H3K27ac and H3K27me3 revealed that ID1 gene regulatory regions are epigenetically poised for upregulation in DIPG tissues compared to normal brain, regardless of H3/ACVR1 mutational status. These data support that the developing pons is regionally poised for ID1 activation. Genetic (shRNA) ID1 knockdown in primary human H3.3K27M-DIPG cells (DIPG007) resulted in significantly reduced invasion and migration in vitro. Additionally, DIPG-ID1-KO cells showed improved sensitivity to radiation therapy. Phospho-kinase array analysis of DIPG cells revealed that Akt and WNK1 activity were significantly downregulated upon ID1 knockdown, which was previously shown in lung tumors. Treatment of DIPG007 cells with cannabidiol (CBD) reduced ID1 expression levels and viability/proliferation of DIPG cells in vitro. ID1 knockdown and CBD treatment studies in vivo are ongoing. In summary, our findings indicate that multifactorial (genetic and regional) epigenetic upregulation of ID1 drives DIPG invasiveness and targeting ID1 using CBD may be a potential strategy for the treatment of DIPGs.